Examining the Impact of Problem-Based and Project-Based Learning on University Students' Self-Confidence and Writing Skills - Irma Suryani; Priyanto Priyanto; Julisah Izar (STAI Hubbulwathan Duri, 2024)
This study aimed to examine the impact of project-based learning (PBL) and problem-based learning (PjBL) on students' self-confidence and short story writing ability in the Primary Teacher Education department at FKIP, Jambi University. The research included 161 second-semester students and employed a quasi-experimental design with nonequivalent pre-test and post-test control groups. Instruments used were pre-tests and post-tests, and data analysis included Normality Test, Homogeneity Test, and Hypothesis Test. The findings indicated that both PBL and PjBL positively influenced students' short story writing abilities. Additionally, self-confidence significantly impacted students' writing skills. An interaction effect was observed between the learning models and self-confidence in writing ability. The two-way ANOVA results of the post-test for the experimental groups (PBL and PjBL) and the control group showed a significance value of 0.014 (0.05), indicating a rejection of the null hypothesis and acceptance of the alternative hypothesis. Thus, the application of PBL and PjBL models significantly improved the short story writing abilities of FKIP students at Jambi University.